“La victoria de la técnica,” According to Ortega y Gasset (An Alternative to Heidegger) - Conill Sancho, Jesús (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2013)
Ortega y Gasset's "Mediation on Technique" is part of his historical diagnostic of modern and contemporary life, wich we can resume by means of the expression "the victory of technique". But, secondly, Ortegian reflections upon technique is decisive for understanding human being, its reason and universal history. And, thirdly, it represents an alternative to the herdeggerian way, not only in relation to technique, but to philosophical thinking in general, although wothout accepting naturalism as way out.